Pengaruh Subtitusi Pakan Komersil dengan Ampas Kelapa Terhadap Pertumbuhan Jangkrik Alam (Gryllus sp) - Trisnawati, Indah Nurlita; Harlita, Harlita (Universitas Sebelas Maret, 2022)
Coconut pulp is expected to be used as an alternative feed with a more economical price that can be used for crickets. This research aimed to determine the effect of substitution of commercial feed with coconut pulp on the growth of crickets (Gryllus sp). This research took place in Cemoro, Ketitang Village, Nogosari District, Boyolali, Central Java from July to August 2022. This research used experimental methods and a Completely Randomized Design (CRD). There were four ration formulation treatments in the research, namely: P0 = 100% commercial feed, P1 = 95% commercial feed and 5% coconut pulp substitution, P2 = 90% commercial feed and 10% coconut pulp substitution, P3 = 85% commercial feed and 15 % substitution of coconut pulp. The feed treatment was given for 30 days by feeding twice a day in the morning and evening with sixteen repetitions of jangkrik alam in each treatment. Data on body weight and length were analyzed by One Way ANOVA at a significance level of 5%. The results showed that each treatment was not significantly different in body weight and body length of crickets (P>0.05). The substitution of coconut pulp flour into the commercial rations of crickets (Gryllus sp) can be given up to a level of 15% without affecting the body weight and length of the crickets.